Immunoprecipitation and MALDI-MS identification of lithocholic acid-tagged proteins in liver of bile duct-ligated rats - Shigeo Ikegawa; Tetsushi Yamamoto; Hiromi Ito; Shunji Ishiwata; Toshihiro Sakai; Kuniko Mitamura; Masako Maeda (Journal of Lipid Research, 2008)
Formation of covalently bound protein adducts with lithocholic acid (LCA) might explain LCA's known carcinogenic properties and hepatotoxicity. We performed studies aimed at isolating and identifying hepatic proteins tagged with LCA, presumably via the ε-amino group of lysine residues. Antibodies recognizing the 3α-hydroxy-5β-steroid moiety of LCA were generated by immunizing rabbits with immunogens in which the carboxyl group of LCA was coupled to BSA via a 6-aminohexanoic acid and/or succinic acid spacer. The resulting antibodies reacted with N-α-(t-butoxycarbonyl)-l-lysine-ε-LCA, the amidated and nonamidated forms of LCA, as well as synthetically prepared LCA adducts with ovalbumin and lysozyme. Proteins tagged with LCA in the liver of bile duct-ligated rats were isolated by immunoprecipitation using these antibodies. Proteins were isolated by two-dimensional electrophoresis, and their structure was identified using matrix-assisted laser desorption ionization time-of-flight mass spectrometry and computer-assisted programs. Proteins labeled with LCA were Rab-3, Rab-12, Rab-16, and M-Ras. Rab proteins are Ras-like small GTP binding proteins that regulate vesicle trafficking pathways. The covalent binding of the Rab proteins with LCA may influence vesicular transport or binding of vesicles to their cognate membrane and may contribute to LCA-induced liver toxicity.